REASONS FOR SCHOOL ESCAPE FROM THE PERSPECTIVE OF TEACHERS AND STUDENTS OF THE INTEGRATED ELECTRONICS TECHNICAL COURSE AT THE FEDERAL INSTITUTE OF ALAGOAS ON CAMPUS MACEIÓ (Research, Society and Development, 2022)
This article intends to understand school, dropout from the perspective of teachers and students within the Integrated Technical Course of Electronics of the Federal Institute of Alagoas, at Campus Maceió, in order to alleviate the problem in the context of the course, building proposals that help the student stay in the integration of studies. The study methodology has a quantitative and qualitative approach. Data were collected in 2020 and 2021 by applying online questionnaires, made possible by google forms, sent to 66 teachers of general and technical training who teach classes in the integrated electronics course and to 194 enrolled students. It is observed in the field research recurrence referring to the need to expand the continuous and pedagogical training of teachers and other school actors, to resize the lack of articulation between sectors, to strengthen public education policies, attention to the socioeconomic problems of students, to encourage greater family participation, the need to readjust physical spaces and reactivate the school food and nutrition sector, propose strategies that help those who by social imposition need to reconcile study and work and finally plan a wide dissemination of the nature of the courses offered at IFAL, in order to to prevent the lack of identification of students with the course they are taking. It is understood that this problem is also associated with the diversity of professionals and students who make up the Federal Institutes, as is verified in other realities by scholars on the subject. Finally, this problem becomes characteristic of the dynamism of inclusion.